Kepatuhan Wajib Pajak yang Dipengaruhi Kualitas Pelayanan, Sosialisasi Pajak dan Sanksi Pajak - Chaeru Syahru Ramdani; Adi Sofyana Latif; Muhamad Eko Ari Wibowo; Rananda Septanta (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid growth of e-commerce activities in Indonesia has increased the number of individual taxpayers conducting business through online platforms, particularly in urban areas such as Jakarta. This development presents challenges for tax authorities in ensuring taxpayer compliance, making service quality and tax socialization essential factors in improving compliance behavior. Therefore, this study aims to examine the effect of service quality and tax socialization on individual taxpayer compliance, as well as the moderating role of tax sanctions in this relationship. This research adopts a quantitative approach using a survey method. The population consists of individual taxpayers engaged in e-commerce businesses in Jakarta. A simple random sampling technique was employed, resulting in 117 respondents. Data were collected through structured questionnaires distributed via Google Forms and delivered directly to respondents through WhatsApp and email. The collected data were processed using SPSS version 25. Data analysis was conducted through descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis to test the proposed hypotheses. The results of the study indicate that service quality and tax socialization have a significant positive effect on individual taxpayer compliance. However, tax sanctions are not able to directly moderate the influence of service quality and tax socialization on taxpayer compliance. These findings suggest that improving service quality and strengthening tax socialization programs are more effective strategies for enhancing compliance among e-commerce individual taxpayers.